Central venous pressure dynamics in neonates with hypoxic-ischemic encephalopathy: insights into high mean airway pressure, PPHN, and ECMO management - Kurimoto, Tomonori; Takuya, Tokuhisa; Kibe, Masaya; Harumatsu, Toshio; Ohashi, Hiroshi; Yamamoto, Tsuyoshi; Hirakawa, Eiji (Frontiers in Pediatrics, 2025)
IntroductionCentral venous pressure (CVP) monitoring provides valuable insights into hemodynamic changes; however, its application in neonates with hypoxic-ischemic encephalopathy (HIE) undergoing advanced therapies remains underexplored. This study aimed to evaluate the dynamics of CVP under varying conditions, including high mean airway pressure (MAP), persistent pulmonary hypertension of the newborn (PPHN), and treatment with inhaled nitric oxide (iNO) and extracorporeal membrane oxygenation (ECMO).MethodsThis retrospective study included 18 neonates diagnosed with HIE, who received brain hypothermia therapy and had umbilical venous catheters (UVC) appropriately placed for CVP monitoring. CVP values were analyzed in relation to high MAP (≥10 cmH₂O), PPHN status, and pre- and post-therapeutic interventions such as iNO and ECMO. Statistical comparisons were performed using Mann–Whitney U tests for continuous variables, with significance set at p < 0.05.ResultsNeonates in the high MAP group exhibited significantly higher mean CVP values than those in the normal MAP group (6 vs. 5 mmHg, p = 0.03). In the PPHN + high MAP group, the mean CVP, oxygenation index, and FiO₂ levels were markedly elevated compared with the high MAP group without PPHN. iNO administration significantly reduced the mean CVP (7 mmHg pre-iNO vs. 4 mmHg post-iNO, p = 0.04), whereas VV-ECMO initiation resulted in an increased CVP (mean CVP: 8 mmHg pre-ECMO vs. 13 mmHg post-ECMO, p = 0.03).DiscussionCVP monitoring via UVC provides critical information on hemodynamic changes in neonates with HIE, particularly under high MAP and PPHN conditions. While iNO effectively reduced CVP and improved oxygenation, VV-ECMO led to elevated CVP, likely due to the return cannula flow. These findings underscore the need for optimized cannula placement and ventilatory strategies to minimize hemodynamic instability during advanced neonatal therapy.